2007
DOI: 10.1063/1.2786613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transition from slip to free molecular flow on gas transport in porous media

Abstract: Absence of subcritical instabilities and global nonlinear stability for porous ternary diffusive-convective fluid mixtures Phys. Fluids 24, 104101 (2012) Capillary filling dynamics of water in nanopores Appl. Phys. Lett. 101, 153112 (2012) Division by fluid incision: Biofilm patch development in porous media Phys. Fluids 24, 091107 (2012) Core-flood experiment for transport of reactive fluids in rocks Rev. Sci. Instrum. 83, 084501 (2012) On a singular incompressible porous media equationTraditional models, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…(c) Knudsen diffusivity coefficient from Bravo [40], and the present D p , the predicted results by Kalarakis et al [41] are also presented in Fig. 7 and compared with the present DSMC data at ε = 0.75.…”
Section: B Apparent Permeability For Various Porositiesmentioning
confidence: 66%
See 2 more Smart Citations
“…(c) Knudsen diffusivity coefficient from Bravo [40], and the present D p , the predicted results by Kalarakis et al [41] are also presented in Fig. 7 and compared with the present DSMC data at ε = 0.75.…”
Section: B Apparent Permeability For Various Porositiesmentioning
confidence: 66%
“…Jones [39] experimentally found b ∝ K ∞ −0.36 ; Bravo [40] considered b as a function of K ∞ and the Knudsen diffusivity coefficient, and the latter could also be correlated as a function of K ∞ . However, the effect of pore-scale geometry features was not included in these correlations.…”
Section: B Apparent Permeability For Various Porositiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For low permeability porous media, Jones (1972) found that the Klinkenberg coefficient b and the liquid permeability K 0 have the relation, b ∝ K −0.36 0 . Bravo (2007) developed the generalized model of the Klinkenberg coefficient b for the whole range of the Knudsen number. In his model, the Klinkenberg coefficient b is a function of the Knudsen number.…”
Section: Introductionmentioning
confidence: 99%
“…Circumstances are not necessarily identical for a network of channels. We require at least a second order model, which leads to κ varying inversely with the pressure (1/p) 2 [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%